The influence of a methylated-Î²-Cyclodextrin on the solubility and photostability of midazolam in aqueous solution,Influence of a methylated-B-Cyclodextrin on the solubility and photostability of midazolam in aqueous solution - Lebete, Mosimotsana Leah (Rhodes University, Faculty of Pharmacy, Pharmacy, 2001)
Midazolam, used clinically as an anticonvulsant, anxiolytic, muscle relaxant and sedative is a photolabile imidazo-benzodiazepine which is marketed under the trade names DormicumÂ® and HypnovelÂ® as tablets and injectables. Because of an aqueous solubility of < 0.1 mg/ml above pH 4, the preparation of aqueous dosage formulations near physiological pH, requires a solubilizer. The aim of this study was thus to prepare a 10 mg/ml midazolam aqueous solution for topical application using randomly-methylated-pcyclodextrin (RAMEB), considered to be a suitable candidate as a solubilizer because of its absorption enhancing properties, and to investigate its effect on both the solubility and the photostability of midazolam. Solubility studies of midazolam (excess of 15 mg/ml) in the presence of 0, 5,10,20, 30% m/v of RAMEB at pH 5.0 and pH 5.8 (phosphate buffer) were undertaken and the results analyzed using a UV method validated for linearity, accuracy, precision and specificity. A stability-indicating HPLC method was developed and validated (precision and accuracy, linearity, range, limit of quantitation, specificity, robustness and ruggedness) for application to kinetic photostability studies and the identification of photodegradants by LC-MS. Forced degradation studies were carried out at concentrations of 0.5 mg/ml of midazolam instead of the target concentration of 10 mg/ml because of the acceleratory effect of the decreased concentration on the rate of photodegradation. The solutions of midazolam with and without RAMEB were irradiated at 550 W/mÂ² for 12 hrs in order to degrade the drug to Â± 10% of the original concentration. The UV method proved to be valid in terms of linearity with a correlation coefficient of 0.9998, precise and accurate, and specific for the determination of midazolam in the presence of RAMEB. The results of the phase solubility studies indicated that desired solubility of 10 mg/ml was achieved with 30% m/v RAMEB at pH 5.0. RAMEB slightly decreased the photostability of midazolam, the rate constants being 0.137 and 0.154 hrâ »Â¹ in the absence and presence of RAMEB, respectively. LC-MS analysis revealed that one of the major photoproducts in the presence and absence of RAMEB was N-desalkylflurazepam, a starting material in the synthesis of midazolam. RAMEB inhibited formation of some photoproducts and introduced two new photoproducts, a dimer and an addition product. The difference in the nature of these photoproducts formed may be attributed to the ability of RAMEB to provide conformational control and to stabilize free radicals. Although RAMEB improved the solubility of midazolam to the target concentration, photostability is decreased with the presence of different photoproducts. These studies have however provided information on the overall photostability of midazolam, the identity of its photodegradants and the photodegradation pathway in the presence and absence of RAMEB, and may be used for further method development and validation for the analysis of aqueous dosage forms containing RAMEB as a solubilizer.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Midazolam -- Solubility